2015
DOI: 10.1128/jvi.01298-15
|View full text |Cite
|
Sign up to set email alerts
|

A Dynein Light Chain 1 Binding Motif in Rabies Virus Polymerase L Protein Plays a Role in Microtubule Reorganization and Viral Primary Transcription

Abstract: Rabies virus (RABV) polymerase L together with phosphoprotein P forms the PL polymerase complex that is essential for replication and transcription. However, its exact mechanism of action, interactions with cellular factors, and intracellular distribution are yet to be understood. Here by imaging a fluorescently tagged polymerase (mCherry-RABV-L), we show that L accumulates at acetylated and reorganized microtubules (MT). In silico analysis revealed a dynein light chain 1 (DLC1) binding motif in L that could m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…Leader RNA can bind La protein which may inhibit cellular RNA synthesis ( Kurilla et al, 1984 ), thus inhibited the viral replication. And L protein of an attenuated vaccine strain SAD B19 can bind to a dynein light chain 1 (DLC1) acted as a transcription enhancer ( Bauer et al, 2015 ). Both of them decreased the viral replication and stimulated the viral transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Leader RNA can bind La protein which may inhibit cellular RNA synthesis ( Kurilla et al, 1984 ), thus inhibited the viral replication. And L protein of an attenuated vaccine strain SAD B19 can bind to a dynein light chain 1 (DLC1) acted as a transcription enhancer ( Bauer et al, 2015 ). Both of them decreased the viral replication and stimulated the viral transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was previously reported that the balance of transcription and replication in RABVinfected cells is regulated by the M protein (6), suggesting direct or indirect interaction between L and M proteins. Interaction of the RABV L protein with host cellular molecules also plays an important role in the propagation cycle: Bauer et al (7) recently reported that the RABV L protein has a dynein light chain 1 binding motif that mediates the interaction of the L protein with cytoskeletal microtubules and also that the interaction is involved in the efficient primary transcription by RABV.…”
mentioning
confidence: 99%
“…This protein is involved in the movement of negative organelles down the length of the microtubules [ 33 ]. Similarly, the rabies viral polymerase L forms a binding complex with dynein light chain 1 (DLC1), which is involved in the linking, modification, and post-translational modification of microtubules and in the regulation of the primary transcription of rabies virus [ 34 ]. This demonstrates that the dynein can be involved in the axonal transport of rabies virus along the length of the microtubules through the neuronal cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A link has been demonstrated between DLC1 and the MAP proteins in the direct binding to tubulin dimers [ 35 ]. This finding suggests that the virus not only uses the microtubule network during entry but also actively manipulates the cytoskeleton and associated proteins to achieve rapid and efficient transport [ 34 ]. It is possible that overexpression of MAP2 and NF-H is induced by DLC1 or by expression of a viral protein, as occurs in the post-translational modification associated with DLC1-polymerase L [ 34 ], DLC8, and P protein [ 33 ], and in the transport mediated by p75NTR [ 32 ].…”
Section: Discussionmentioning
confidence: 99%